Crystal structure of the (E)-O-methyl-N-phenyl-thiocarbamate – 4,4′-bipyridine (1/1), C18H17N3OS - Yeo, Chien Ing *; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C18H17N3OS, monoclinic, C2/c (no. 15), a=13.4754(3) Å, b=13.8997(3) Å, c=18.0300(4) Å, β=107.202(3)°, V =3226.03(13) Å3, Z =8, Rgt(F)=0.0341, wRref(F2)=0.0878, T =100(2) K.